Analisa Account Receivabel Days, Account Payable Days, dan Investor Days Terhadap Prioritas - Ade Ghofir; Amanda Ayu Ningsih (Prisani Cendekia, 2022)
This study aims to determine the analysis of accounts receivable days, account payable days and inventory days on profitability. The population in this study is a manufacturing company in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange, the number of this population is 14 companies. The sampling technique used in this study is non-probability sampling with purposive sampling, namely the selection of samples based on certain criteria. . The collected data is processed by multiple regression analysis method with SPSS. Researchers chose by taking into account several criteria for population members that were adjusted for the purpose of the study, Account Receivable Days had no and insignificant effect on Profitability